ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN CHATIME (STUDI PADA MAHASISWA UPN VETERAN JAKARTA) - Noah Stanly Dwinanda, (2022)
In Indonesia, the bubble tea beverage industry is an industry that has enormous potential to grow rapidly. This cannot be separated from the role of the millennial generation, who are the main consumers of this industry. The purpose of this research is to examine and prove whether or not there is an effect of electronic word of mouth, price, and promotion on purchasing decisions. Quantitative research is a type of this research. UPN Veteran Jakarta students who have purchased Chatime products are used as the research population. By using a non-probability sampling with purposive sampling, a sample of 100 respondents whose data was obtained through online questionnaires. The data obtained was analyzed using the PLS (Partial Least Square) technique by utilizing SmartPLS 4.0 software. The results of data processing prove that electronic word of mouth and promotion has a significant effect on purchasing decisions with an original sample value of 0.202 and 0.374, while price has no significant effect on purchasing decisions with an original sample value of 0.149.